A Theoretical Study on the Influence of the Functional Group Electronic Effect on the Electron Mobility of Cross-Linked Polyethylene - Yang Du; Hui Zhang; Xia Du; Yan Shang; Xuan Wang; Qingguo Chen; Zesheng Li (Applied Sciences)
The effect of electron-donating and electron-withdrawing groups grafted onto polyethylene on electron mobility was studied using density functional theory. In order to ensure the accuracy of the calculation results, 17 basis sets from six methods were screened. 3-methylpentane was selected as the cross-linked polyethylene model. Compared with the experimental values, the theoretical calculation results show that wB97XD/6-311G(d,p) is more suitable for studying the electron mobility system. The roles of electron-donating and electron-withdrawing functional groups were studied. The results show that the electron mobility of grafting nitrobenzene (Ebnb) to polyethylene is the smallest among the studied molecules. As the ability of electron-donating groups increases, the electron mobility gradually increases, while the addition of the electron-withdrawing group reduces the electron mobility and the electron mobility gradually increases with increasing temperature. This investigation is expected to provide reliable information for the development of insulation materials for cables.